1992
DOI: 10.1021/om00060a028
|View full text |Cite
|
Sign up to set email alerts
|

Iron carbonyl promoted conversion of .alpha.,.omega.-diynes to (cyclopentadienone)iron complexes

Abstract: An efficient high-yielding procedure is described for the intramolecular carbonylative coupling of , -diynes to give cyclopentadienone-Fe(CO)3 complexes. Exchanging one CO ligand with PPh3 affords control over the manipulation of , '-trimethylsilyl-substituted cyclopentadienone complexes. The preparation of , -diynes with a hydroxy group adjacent to one alkyne unit leads to modest stereocontrol upon cyclization forming the Fe(CO)3 complex. The hydroxy-substituted complex was oxidized to ketone. Borohydride red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(39 citation statements)
references
References 2 publications
3
35
1
Order By: Relevance
“…Heating a 1:2 mixture of the diyne and Fe(CO) 5 in a microwave reactor tube for 15 min resulted after cooling, venting, filtration and flash chromatography in the isolation of the desired cyclopentadienone complexes [{η 4 -C 4 R 2 C(O) C 4 H 8 }Fe(CO) 3 ] (1-5) as yellow crystalline solids in 70-80% yields (Scheme 3). Yields of 1 and 2 are significantly higher than those of 57 and 52%, respectively, reported previously [46][47][48], suggesting that the significantly lower reaction times lead to less product decomposition. While we generally carried out reactions using 0.8 mmol of diyne, we noted similar yields when the reaction scale was doubled along with the irradiation time.…”
Section: Synthesis and Characterisation Of Cyclopentadienone Complexescontrasting
confidence: 55%
See 2 more Smart Citations
“…Heating a 1:2 mixture of the diyne and Fe(CO) 5 in a microwave reactor tube for 15 min resulted after cooling, venting, filtration and flash chromatography in the isolation of the desired cyclopentadienone complexes [{η 4 -C 4 R 2 C(O) C 4 H 8 }Fe(CO) 3 ] (1-5) as yellow crystalline solids in 70-80% yields (Scheme 3). Yields of 1 and 2 are significantly higher than those of 57 and 52%, respectively, reported previously [46][47][48], suggesting that the significantly lower reaction times lead to less product decomposition. While we generally carried out reactions using 0.8 mmol of diyne, we noted similar yields when the reaction scale was doubled along with the irradiation time.…”
Section: Synthesis and Characterisation Of Cyclopentadienone Complexescontrasting
confidence: 55%
“…In other complexes of this type, it is generally the central carbon-carbon bond, C(6)-C(7), which is the shortest within the ring. This is also the case for 4 (both independent molecules) and 3 [C(6)-C(7) 1.421-1.429 Å; C(5)-C(6) and C(7)-C(8) 1.432-1.453 Å] and has been attributed to the back-bonding interaction between the metal centre and the diene LUMO [46][47][48]. The situation is less clear in 2 where the C(6)-C(7) bond length of 1.430(2) Å is shorter than the C(7)-C(8) interaction of 1.446(2) Å but comparable to the C(5)-C(6) vector of 1.429(2) Å.…”
Section: Structural Studiesmentioning
confidence: 62%
See 1 more Smart Citation
“…Reactions were monitored by TLC using aluminum backed silica gel 60 (F254) plates, visualized using UV 254 nm and phosphomolybdic acid 20 4-phenyl-3-butyn-2-yloxy(prop-2-yne) 12b, 21 3-phenyl-2-propyn-1-yloxy(prop-2-yne) 12a, 22 3-phenyl-2-propyn-1-yloxy(3-phenylprop-2-yne) 13a, 23a 4-phenyl-3-butyn-2-yloxy(3-phenylprop-2-yne) 13b, 21 tricarbonyl(2,4-bis(trimethylsilyl)bicyclo[4.3.0]nona-1,4-dien-3-one)iron 6. 8 …”
Section: Methodsmentioning
confidence: 99%
“…This 35 remains to be tested experimentally. Although a racemic process, a very significant breakthrough was reported in 2007 by Casey and Guan, 24,25,3 who found that the known 26,27 cyclopentadienyl iron hydride complex 11, itself prepared from the iron tricarbonyl cyclone complex 12, was effective at the catalysis of carbonyl and imine 45 hydrogenation under relatively mild conditions (Figure 4). There are analogies in the speculated mechanism of the catalytic cycle to that of the reactions catalysed by the ruthenium-based Shvo catalyst 13, which has also been extensively studied by complex.…”
Section: Introductionmentioning
confidence: 99%